Critical cities. Learning from extreme urban contexts, paths for sustainable urban planning in New Delhi and beyond - Santos, S. (2019)
New Delhi is the second largest megacity in the world, housing around 26 million inhabitants, it’s also a city of extremes.1 Uneven growth and social segregation, massive urbanization, environmental threats, lack of public services, infrastructural weaknesses are a daily routine, and not some future dystopian scenario. 2 According to Delhi Master Plan (2021), only 24% of the population lives in considered legal areas, with the remaining 76% of the population inhabiting unauthorized areas, with poor access to basic services such as house, water, electricity, health or education. 3 The majority of urban population seems to have been forgotten across time or doomed to social-spatial exclusion, enunciating an outstanding gap between planning practice and the dynamics and needs of the city. We may question whether the perpetuation of this gap hasn’t been always embedded in planning and policy practice, constituting an echo of political, economic, institutional and scientific ‘influences’ ? from the West to the East or a mirror of the Indian fragmented society. 4 Three urban planning moments will be revisited in this paper, corresponding also to specific historical contexts, urban models, polices and regulations: Colonial planning driven by the interests of the British empire; modernist planning motivated by post-independence democracy; and, more recently, what one may venture to categorize as neoliberal planning, boosted by economic structural adjustments in the 90’s.56 It’s intended to demonstrate the nexus between the exercise of planning and police making and the growing detachment between a ‘planned city’ and an ‘unplanned city’, with its extreme consequences and risks. Finally, the paper presents some concluding remarks on the importance to critically analyse the permeability of concepts, models and practices to external influences, and how urban planning field may be undermined and/or undermining the solving of urban challenges around the World. This paper presents preliminary results of a research exchange at the Centre for the Study of Science Policy, Jawarlal Nehru University (New Delhi) under the European Marie Currie project "Crossing Borders. Knowledge, Innovation and Technology transfer across borders". Main results are based on literature review, consultation of planning/policy tools and the analysis of a set of interviews conducted to researchers from several disciplinary fields and to public institutions related to urban planning.